Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Maggie Swaggerty and Frank Swaggerty Frank is the son of Mattie Watkins Swaggerty; Mattie was Albert Watkins' aunt.